2018
DOI: 10.1186/s40494-018-0214-1
|View full text |Cite
|
Sign up to set email alerts
|

Materials characterization of the Ruby Slippers from the 1939 classic film, The Wizard of Oz

Abstract: This article presents a comprehensive materials characterization of a pair of Ruby Slippers used in the 1939 classic film The Wizard of Oz, which has been one of the most popular objects on exhibition at Smithsonian's National Museum of American History (NMAH) since it entered the collection in 1979. The shoes have been on almost constant display with few instances for study during its time at NMAH, and they remain one of the most visited objects within the museum. Plans for an upcoming permanent exhibit, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…After final centrifugation at 12,000 rpm, 30 µL of the supernatant was transferred to an insert in an auto-injector vial and 20 µL was injected onto the HPLC column. This extraction method, compared to the one used for HPLC-DAD, was optimized to provide good recovery for a very broad range of categories of natural and synthetic dyes [27,60].…”
Section: Hplc-dad-msmentioning
confidence: 99%
“…After final centrifugation at 12,000 rpm, 30 µL of the supernatant was transferred to an insert in an auto-injector vial and 20 µL was injected onto the HPLC column. This extraction method, compared to the one used for HPLC-DAD, was optimized to provide good recovery for a very broad range of categories of natural and synthetic dyes [27,60].…”
Section: Hplc-dad-msmentioning
confidence: 99%
“…El estudio de las causas de degradación de los bordados aplicados tanto en alta costura como en moda histórica han sido desde hace unos años el eje principal de investigación dentro de las colecciones museísticas (Porcel Ziarsolo 2012;Koek 2018;Rodriguez Salinas, Albertini y Ferrazza 2021;Douglas et at. 2018;Paulocik y Williams 2010).…”
Section: Introductionunclassified
“…Several studies are reported in the literature on the identification of synthetic organic dyes and pigments in paintings, or in paint and textile mockups, while only few are dedicated to synthetic organic dyes detection in 19th historical textile archives and modern costumes. In these cases, synthetic dye recognition was performed by 3D Fluorescence [32], Raman and Surface Enhanced Raman Spectroscopy (SERS) [33] and High Performance Liquid Chromatography coupled with Diode Array Detector and Mass Spectrometer detector (HPLC-DAD-MS) [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%